Self-Esteem and Peer Social Support: How Do They Contribute to High School Students' Academic Hardiness? - Aprillia Dewi Puspa Lestari; Eni Rindi Antika (State Islamic University (UIN) Salatiga, 2023)
Several factors, including internal and external factors, often cause academic hardiness in students. This research aims to analyze the influence of student self-esteem as a student's internal factor and peer social support as a student's external factor on students' level of academic hardiness. This research uses a quantitative approach with an ex post facto design. This research was conducted on 350 public high school students in Central Semarang District who were taken using the Proportionate Stratified Random Sampling technique. The instruments used in this research were the self-esteem scale (29 valid items α = .926), the peer social support scale (27 valid items α = .895), and the academic hardiness scale (24 valid items α = .845). The data was analyzed using multiple regression tests and met the classical test. The results show p-value = .000 (p <0.05). The coefficient of determination value shows that self-esteem and social support from peers influence academic hardiness by 44,6%. Meanwhile, some of it is influenced by other variables outside the research. This research impacts guidance and counseling teachers and counselors so they can provide services to increase self-esteem, peer social support, and student academic hardiness.